Maximizing surveillance through spatial characterization of marine mammal stranding hot spots. Issue 4 (5th May 2020) - Olson, Jennifer K.; Aschoff, John; Goble, Alice; Larson, Shawn; Gaydos, Joseph K.
Abstract: Spatial analyses of marine mammal stranding data can be used to identify stranding patterns and improve surveillance and monitoring. Using ArcGIS and SaTScan, we analyzed 12 years (2002–2014) of dead beachcast marine mammals from San Juan County, Washington, to better understand patterns of carcass deposition. We plotted the locations for 631 dead marine mammals and aggregated strandings into 1, 000 m segments of shoreline. "Hot spots" included beach segments with significantly higher carcass deposition according to the Getis‐Ord Gi* statistic in ArcGIS or beach segments that were encompassed by significant spatial clusters using the discrete Poisson model in SatTScan. We identified 52 hot spots for harbor seals ( Phoca vitulina ) in ArcGIS and 62 hot spots in SaTScan with 81% agreement between methods. Carcass deposition showed a strong relationship with locations having high proximity to public pedestrian access points, suggesting increased reporting effort in those areas. Stranding frequency was also higher on beach segments with longer fetch and nearly level or gentle slopes. Beaches with these geomorphic characteristics, especially those without high proximity to public access, would be ideal locations to actively survey to improve high quality carcass collection during times of high expected mortality and limited resources.